(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
In the article the content of the concept of psychological and pedagogical manipulation according to the views of various scientists is considered and analyzed. Also, the concept of psychological influence is covered. It was found out what kind of interaction there is between the student and the teacher. Different types of manipulations are identified and briefly characterized. The relevance or its absence in the use of different types of manipulation in the pedagogical process is analyzed. The process of psychological and pedagogical manipulation in educational institutions is studied. The level of awareness of the subjects in the issue of manipulative process is determined.